Fine needle aspiration biopsy: An entrustable professional activity in cytopathology postgraduate training - Harresh B Kumar; Amir M Khan; Vinod K Arora; Navjeevan Singh (Journal of Cytology, 2017)
Context: In the context of competency-based medical education being advocated worldwide, fine needle aspiration biopsy (FNAB) is considered as an entrustable professional activity (EPA). There is no information regarding how much time and training are required to achieve a “competent level” for performing and documenting FNAB in the Indian context. Aim: To determine the time taken by an average postgraduate pathology trainee to become competent in performing FNAB with respect to history taking, clinical examination, and fine needle aspirate adequacy. Settings and Design: A descriptive, retrospective, chart-based audit was conducted in the Department of Pathology. Materials and Methods: FNAB chart records documented during 3 years of postgraduate training by a cohort of 13 postgraduate (PG) resident trainees admitted in 2010 were included in the study. Adequacy rates and criteria for adequacy were defined for the purpose of the study. Statistical analysis: Data was entered in MS Excel and analyzed using the Statistical Package for the Social Sciences version 20.0. The adequacy rates are presented as percentages and time taken to achieve adequacy rates as median values. Results: A total of 3272 charts were audited. Median time taken to achieve 85% adequacy rate for history taking, for clinical examination by the first and the second criteria, and for FNAB were 1 month, 1 month and 3.5 months, and 1 month, respectively. Conclusions: Although the mean time taken to achieve 85% adequacy rates for FNAB was 1 month, there was wide variation in the time durations between the residents to achieve this level.